2020
DOI: 10.1080/17544750.2020.1761848
|View full text |Cite
|
Sign up to set email alerts
|

#PositiveEnergyDouyin: constructing “playful patriotism” in a Chinese short-video application

Abstract: In Chinese political discourse, "positive energy" (zheng nengliang) is a popular expression that has embodied mainstream political ideology in China since 2012. This term has also become prominent on Douyin, a prominent Chinese short-video platform. By June 2018, over 500 Chinese governmental accounts on Douyin had promoted positive energy in videos, and the content was viewed over 1.6 billion times. Douyin even created a separate trending section, Positive Energy, for videos that promoted the dominant state i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 36 publications
2
84
0
Order By: Relevance
“…We found, for instance, that TikTok creators often combined sincere appeals with humorous text or visuals. Such playful sincerity has the practical effect of improving the “palatability, appeal, and dissemination” (Chen et al, 2021, p. 2) of a topic such as climate change, around which discourse is often politically and ideologically charged. Looking at a single isolated TikTok, it is impossible to identify whether it became popular because of the sincere appeal of its message or simply because people found it funny.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…We found, for instance, that TikTok creators often combined sincere appeals with humorous text or visuals. Such playful sincerity has the practical effect of improving the “palatability, appeal, and dissemination” (Chen et al, 2021, p. 2) of a topic such as climate change, around which discourse is often politically and ideologically charged. Looking at a single isolated TikTok, it is impossible to identify whether it became popular because of the sincere appeal of its message or simply because people found it funny.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Douyin clearly bears more marks of Chinese internet regulation than TikTok. As noted above, ByteDance has taken steps to appease the Chinese government, such as including a positive energy section following a domestic controversy (Chen, Kaye, & Zeng, 2020). While officially TikTok does not include infrastructures or policies that can be directly related to the internet governance in mainland China, the platform has been the subject of intense scrutiny in different national contexts, in part due to its Chinese roots.…”
Section: Identity Crisismentioning
confidence: 99%
“…While the Chinese government has been known to influence the content available on Douyin, the evidence of similar influence on TikTok is limited. For example, a 2020 comparative study of the two Bytedance short form video apps found the Chinese government used Douyin to promote Chinese patriotism but there was no corresponding evidence on TikTok (Chen et al, 2020). When Bytedance first began releasing TikTok into markets outside of China in 2017, the platform's content moderation guidelines were aimed at limiting the circulation of all highly controversial materials on the platform.…”
Section: The Geopolitics Of Tiktok's Controversial Rise In the Usmentioning
confidence: 99%